A Bayesian LDA-based Model for Semi-Supervised Part-of-speech Tagging - Toutanova, Kristina; Johnson, Mark (In Proceedings of NIPS, 2008)
We present a novel Bayesian model for semi-supervised part-of-speech tagging. Our model extends the Latent Dirichlet Allocation model and incorporates the intuition that words’ distributions over tags, p(t|w), are sparse. In addition we introduce a model for determining the set of possible tags of a word which captures important dependencies in the ambiguity classes of words. Our model outperforms the best previously proposed model for this task on a standard dataset.